Hyperhomocysteinemia is associated with the risk of venous thromboembolism in patients with mental illness: a case-control study - Wang, Jiaoyan; Zhang, Yingchun; Ren, Keming; Li, Yeping; Ying, Kejing (Frontiers in Psychiatry, 2024)
Objective: The risk of venous thromboembolism in patients with mental illness has been insufficiently addressed. This study aimed to assess the correlation between hyperhomocysteinemia and venous thromboembolism prevalence among this population.Methods: Patients with a diagnosis of mental illness and concurrent venous thromboembolism, admitted to Sir Run Run Shaw Hospital at Zhejiang University School of Medicine between January 2014 and December 2021, were included in the venous thromboembolism group. The control group, approximately twice the size, comprised individuals with mental illness but without venous thromboembolism.Basic clinical data were gathered for both cohorts.Results: In psychiatric patients, elevated D-dimer levels(OR=5.60,95% CI 3.28-10.00), hyperhomocysteinemia (OR=2.37 ,95% CI 1.10-5.14), and hyperprolactinemia(OR= 2.68 ,95% CI 1.12-6.42)were significant risk factors for venous thromboembolism. According to further subgroup analyses, hyperhomocysteinemia is a significant risk factor associated with pulmonary embolism, with an OR of 5.08 (95% CI 1. 20-21.48). An interaction effect between gender and homocysteine level was found, with a p-interaction of 0.022. A subsequent analysis confirmed the association between hyperhomocysteinemia and venous thromboembolism in female psychiatric patients, with an OR of 3.34 (95% CI 1.68-6.65), indicating that hyperhomocysteinemia is a significant risk factor for venous thromboembolism in women.Conclusion: Patients with psychiatric disorders were found to have an elevated risk of venous thromboembolism, which was associated with increased levels of D-dimer, hyperprolactinemia, and hyperhomocysteinemia. A strong correlation between hyperhomocysteinemia and pulmonary embolism was identified in patients with mental illnesses. Furthermore, the study revealed that female psychiatric patients with hyperhomocysteinemia constituted a high-risk group for venous thromboembolism. This finding holds significant clinical implications, suggesting that early preventative measures could be implemented for this high-risk population to reduce the incidence of thromboembolic events during hospitalization for psychiatric patients.